Michael Faraday's 'Chemical notes, hints, suggestions, and objects of pursuit' of 1822 - Faraday, Michael 1791-1867 (P. Peregrinus in association with the Science Museum, 1991)
Transcribed and published here for the first time, this Notebook shows that Faraday's physical achievements emerged from the context of applied laboratory chemistry. It foreshadows many of his most important discoveries and offers a revealing insight into the mind and scientific aspirations of a master experimentalist. The Notebook is significant amongst Faraday's unpublished writings because it served as a place to explore possibilities and questions, rather than simply to record laboratory work.